Corporate Governance, Financial Leverage, and Performance of Sharia Manufacturing Companies on the Indonesia Stock Exchange - Muhamad Umar Mai; Mochamad Edman Syarief; Kristianingsih Kristianingsih (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2021)
This paper discusses the impact of corporate governance on the leverage effect and the leverage effect on corporate performance. The study was conducted on Islamic manufacturing companies on the Indonesia Stock Exchange during the period 2012 to 2018. The data analytics method used Partial Least Square (PLS) which was handled with the WarpPLS application. The results show that almost all proxies of the corporate governance variable negatively affect financial leverage variable, except for the Independent Board of Commissioners (ICB) which has a positive effect on book leverage (BLEV). Furthermore, financial leverage as proxy by book leverage (BLEV) shows a positive effect on market performance (TBQ) and negative effect on book performance (ROA). The financial leverage effect by market leverage variable (VEML) has a negative effect on market performance (TBQ) as well as on accounting performance (ROA). An important implication of this study is that in general, Shariah manufacturing companies that are more profitable tend to reduce their financial leverage, and investors can better recognize the relationship between financial leverage decisions and firm performance.